Uniform spheroidal nanoassemblies of magnetite using Tween surfactants: influence of surfactant structure on the morphology and electrochemical performance1. Issue 7 (21st February 2015) - Maqbool, Qysar; Singh, Chanderpratap; Paul, Amit; Srivastava, Aasheesh
<x xml:space="preserve">Abstract</x> Uniform spherical nanoassemblies of Fe3O4 prepared using tween surfactants.